The Implications of Foreign Investment Limitations on 'The End Justifies the Means' Practices within the Indonesian Investment Sector - Akbar, M. Aidil; Ritonga, Wildan Ambron; Putra, Rifqi Pratama (Rechtsvinding, 2025)
This study aims to analyze the implications of Presidential Regulation (Perpres) Number 49 of 2021 on the emergence of "the end justifies the means" practices by foreign investors within joint venture companies in Indonesia. Although this regulation provides investment facilities to stimulate national economic growth, certain strategic sectors remain subject to foreign ownership restrictions. A primary issue arises when domestic investors face financial constraints in fulfilling the required majority shareholding portions. This condition leads to legal smuggling practices by foreign investors seeking full corporate control, notably through nominee shareholder mechanisms. This legal research highlights how the capital disparity between foreign and domestic investors triggers the use of trusteeship agreements or dummy corporations, which are strictly prohibited under Indonesian law. The findings suggest the necessity of strengthening legal frameworks and oversight to balance foreign investment interests with national economic sovereignty